The Mediation of Islamic Social Reporting to Influence the Islamic Corporate Governance on Firm Value (Study on Islamic Banking in Southeast Asia 2012-2016) - Sardiyo Sardiyo; Martini Martini (Universitas Muhammadiyah Ponorogo, 2021)
This study investigates Islamic social reporting as an intervening variable between Islamic corporate governance to firm value. The method used purposive sampling with the samples of 11 sharia banks listed on Bursa Malaysia and Indonesia in 2012-2016. The analysis used path analysis with warp partial least square to examine the mediation effect of Islamic social reporting. Indicators for measuring Islamic corporate governance used accountability, transparency, responsibility, and fairness. Indicators measured firm value using price to book value ratio and price to earnings ratio. Indicators for measuring Islamic social reporting used investment and finance, products and services, labor, community, environment, and corporate governance. The results described Islamic corporate governance had a significant positive effect on firm value. Islamic corporate governance showed a significant positive impact on Islamic social reporting. Islamic social reporting had a significant negative effect on firm value, so it is concluded that Islamic social reporting is unable to mediate between the influence of Islamic corporate governance on firm value. This confirms that sharia banking with good Islamic corporate governance would improve Islamic social reporting and firm value, while Islamic social reporting runs well could not respond to investors as information needed in decision making to increase firm value.